A new cave-dwelling species of the genus Triplophysa (Cypriniformes, Nemacheilidae) from southwest China - Zhu, Ting-Ting; Yuan, Feng-Hua; Zhang, Ren-Yi; Zhao, Ya-Hui (Zoosystematics and Evolution, 2025)
Based on morphological and molecular data, we described a new cave-dwelling species, Triplophysa xiuwenensis sp. nov. , from the karst region of southwest China. The new species can be distinguished from its congeners by the following morphological characteristics: body scaleless without pigmentation; eye diameter of HL with 4.6–6.7%; tip of pelvic fin not reaching anus; outer rostral barbel reaching to posterior margin of eyes; 14–15 branched caudal fin rays. Phylogenetic relationships based on the mitochondrial cytochrome b (Cyt b ) gene support the validity of the new species. The discovery of the new species brings the number of cave-dwelling Triplophysa species in Guizhou Province to 15, making it the region with the highest number of Triplophysa cave species in the southwestern karst area.